A voyage with Hitchcock - Pomerance, Murray, 1946- (SUNY Press, 2021)
"Extensive meditations on the theme of the voyage in six Hitchcock films: Psycho, The 39 Steps, The Birds, Dial M for Murder, Rich and Strange, and Suspicion"-- Provided by publisher.
Formerly CIP.
Keywords: Hitchcock, Alfred, -- 1899-1980 -- Criticism and interpretation.; Hitchcock, Alfred, -- 1899-1980; Travel in motion pictures.; Thrillers (Motion pictures) -- History and criticism.; Voyage au cinéma.; Thrillers (Films) -- Histoire et critique.; PERFORMING ARTS / Film / History & Criticism; Thrillers (Motion pictures); Travel in motion pictures; Criticism, interpretation, etc.